Design and Construction of Automized Assembly Application - E.E HTWE; S Hatanaka; T Akiyama (ASEAN Journal on Science and Technology for Development, 2012)
Nowadays the main stream of current automatic process and assembly is on intermittent transportation. Robot control systems can be divided into motion control and force control depending on the work. Assembly work is necessary to consider the state of force applied by detection of the force or moment on the fingers of the gripper. In this project, four groups designed and developed each one of the stages of the workpieces until the final piece was delivered; it was composed of three different workpieces. The mechanism was designed to set the shaft and fasten the screw into a vacancy in a workpiece. The machine was constructed with frame, base plate, support, gripper and workpieces by using CNC milling, turning, drilling and wirecut machine. This paper briefly describes the design analysis of a conveyor, actuator and motor control system.